2004
DOI: 10.1007/s10265-003-0138-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic alterations in Arabidopsis thaliana plants caused by Rhodococcus fascians infection

Abstract: Arabidopsis thaliana (L.) Heynh. plants were challenged with Rhodococcus fascians at several developmental stages and using different inoculation procedures. A variety of morphological alterations was scored on the infected plants; some of them resembled phenotypes of A. thaliana mutants in their shoot apical meristem (SAM) organization. Infection with R. fascians did not affect SAM organization in wild type nor in SAM mutants. Anatomical studies on the new organs formed after infection with R. fascians demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…R. fascians causes various effects in its hosts, including leaf deformation and formation of witches' broom, fasciations, and leafy galls (517,519). The symptoms are caused by the hyperinduction of shoots through activation of dormant axillary meristems and de novo meristem formation, probably as the result of elaborate manipulation of host hormone balances and pathogen-derived auxins and cytokinins (520,521). In contrast to Streptomyces and Rhodococcus, plantpathogenic species in the Actinobacteria genera Clavibacter and Leifsonia are host specific at the species or subspecies level.…”
Section: Interactions Between Actinobacteria and Plantsmentioning
confidence: 99%
“…R. fascians causes various effects in its hosts, including leaf deformation and formation of witches' broom, fasciations, and leafy galls (517,519). The symptoms are caused by the hyperinduction of shoots through activation of dormant axillary meristems and de novo meristem formation, probably as the result of elaborate manipulation of host hormone balances and pathogen-derived auxins and cytokinins (520,521). In contrast to Streptomyces and Rhodococcus, plantpathogenic species in the Actinobacteria genera Clavibacter and Leifsonia are host specific at the species or subspecies level.…”
Section: Interactions Between Actinobacteria and Plantsmentioning
confidence: 99%
“…The reiteration of this process together with the activation of axillary meristems ultimately culminates in the typical leafy gall symptom on tobacco and is correlated with the up-regulation of CYCD3;2 and CYCB1;1 (de O Manes et al, 2001). Also in Arabidopsis, activation of axillary meristems and de novo meristem formation contribute to symptom development (de O Manes et al, 2004;Simó n-Mateo et al, 2006) and are associated with elevated expression of CYCA2;1, CYCB1;1, and CDKA;1 . Here, with the developing Arabidopsis leaf as a model system, we found that during infected leaf development the transcriptional profiles of the tested cell cycle genes all showed a typically biphasic pattern: initial expression was mostly constitutive but increased steadily from 16 dpi onward.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis plants that are infected with the phytopathogenic actinomycete R. fascians display typical phenotypes, such as smaller and serrated leaves, activated axillary and de novo formed meristems, and usually very compact rosettes de O Manes et al, 2004;Simón-Mateo et al, 2006;Depuydt et al, 2008). To gain a genome-wide view of the processes that are involved in disease establishment, we compared the transcriptome of Arabidopsis plants (ecotype C24) infected with the virulent strain D188 with that of plants infected with the nonpathogenic derivative D188-5 as control samples using two-color CATMA microarrays (Crowe et al, 2003;Hilson et al, 2004).…”
Section: Transcriptome Analysis Underlines the Key Role For Cytokininmentioning
confidence: 99%
“…Upon infection with the Gram-positive, cytokininproducing phytopathogen Rhodococcus fascians, the architecture of the plant is drastically changed (Crespi et al, 1992(Crespi et al, , 1994Vereecke et al, 2000Vereecke et al, , 2002aVereecke et al, , 2002bGoethals et al, 2001;de O Manes et al, 2004). Remarkably little is known about the molecular basis of the pathologies of Gram-positive phytopathogens: they do not possess type III secretion systems, the typical Gram-negative effectors have not been identified, and no defense suppression mechanisms have been uncovered (Loria et al, 2006;Robert-Seilaniantz et al, 2007;Gartemann et al, 2008).…”
mentioning
confidence: 99%